A novel solar-assisted heat pump driven by photovoltaic/thermal collectors: Dynamic simulation and thermoeconomic optimization. (15th January 2016) - Calise, Francesco; Dentice d'Accadia, Massimo; Figaj, Rafal Damian; Vanoli, Laura
Abstract: This paper presents a dynamic simulation model and a thermo-economic analysis of a novel polygeneration system based on a solar-assisted heat pump and an adsorption chiller, both driven by PVT (photovoltaic/thermal) collectors. The aim of this work is to design and dynamically simulate a novel ultra-high efficient solar heating and cooling system. The overall plant layout is designed to supply electricity, space heating and cooling and domestic hot water for a small residential building. The system combines solar cooling, solar-assisted heat pump and photovoltaic/thermal collector technologies in a novel solar polygeneration system. In fact, the polygeneration system is based on a PVT solar field, coupled with a water-to-water electric heat pump or to an adsorption chiller. PVT collectors simultaneously produce electricity and thermal energy. During the winter, hot water produced by PVT collectors primarily supplies the evaporator of the heat pump, whereas in summer, solar energy supplies an adsorption chiller providing the required space cooling. All year long, solar thermal energy in excess is converted into DHW (domestic hot water). The system model was developed in TRNSYS environment. 1-year dynamic simulations are performed for different case studies in various weather conditions. The results are analysed on different time bases presenting energetic, environmental and economic performance data. Finally, a sensitivity analysis and a thermoeconomic optimization were performed, in order to determine the set of system design/control parameters that minimize the simple pay-back period. The results showed a total energy efficiency of the PVT of 49%, a heat pump yearly coefficient of performance for heating mode above 4 and a coefficient of performance of the adsorption chiller of 0.55. Finally, it is also concluded that system performance is highly sensitive to the PVT field area. The system is profitable when a capital investment subsidy of 50% is considered. Highlights: A trigeneration system for a residential building is presented. System includes: PVT collectors, solar-assisted heat pump, adsorption chiller. The system provides space heating/cooling and domestic hot water. The space cooling demand is mainly supplied by adsorption chiller. The system simple pay back period is about 8 years in case of incentive.